Medical education - Geraldo Brasileiro Filho (University of São Paulo, 2013)
Over the years, producing good physicians has been a huge challenge worldwide. Over the last two decades, this issue has gained notorious interest in Brazil, due to the uncontrolled expansion of medical schools, many of which are unable to adequately prepare students for professional practice.